Exploration and Reflection on the Integration of Contemporary Installation Artworks into Rural Construction - Yu, Mo (Transactions on Social Science, Education and Humanities Research, 2024)
With the acceleration of urbanization, rural development is facing many challenges, but at the same time, it is also pregnant with unlimited opportunities. As an innovative and unique art form, contemporary new installation art is gradually attracting people’s attention. In this paper, we will discuss how to integrate new contemporary installation art works into rural construction, bring new cultural flavor and development power to the countryside, and open up a new pattern of artistic rural construction.